Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.watres.2013.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of artichoke wastewaters by integrated membrane process

Abstract: 13The purpose of this work was to analyse the potentialities of an integrated membrane 14 system for the recovery, purification and concentration of polyphenols from olive mill 15 wastewater (OMW). The proposed system included some well-known membrane 16 operations such as microfiltration (MF) and nanofiltration (NF), as well as others not 17 yet investigated for this specific application, such as osmotic distillation (OD) and 18 vacuum membrane distillation (VMD). 19The OMW was directly submitted to a MF oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 39 publications
5
44
0
Order By: Relevance
“…Basically, even when our study followed the basic preparation instruction to carry out a common Nixtamalization process, the physicochemical composition of Nejayote depends of the lime quality, type of grain, grain quality, cooking time, and some other parameters as were reported by Gutiérrez-Uribe et al (2010) and Ruiz-Gutiérrez et al (2010). The content of polyphenols on Nejayote was of about 1190.74 mg mL −1 higher content than reported as the content of low molecular weight polyphenols on other wastewaters as artichoke wastewater of 516.7 mg mL −1 (Conidi et al, 2014) and olive mill wastewaters of 211.80 mg mL −1 (Garcia-Castello et al, 2010). Similar content compared to our study was observed by Cassano et al (2013), 1409 mg mL −1 in terms of total polyphenols in olive mill wastewaters.…”
Section: Nejayote Compositionmentioning
confidence: 95%
See 2 more Smart Citations
“…Basically, even when our study followed the basic preparation instruction to carry out a common Nixtamalization process, the physicochemical composition of Nejayote depends of the lime quality, type of grain, grain quality, cooking time, and some other parameters as were reported by Gutiérrez-Uribe et al (2010) and Ruiz-Gutiérrez et al (2010). The content of polyphenols on Nejayote was of about 1190.74 mg mL −1 higher content than reported as the content of low molecular weight polyphenols on other wastewaters as artichoke wastewater of 516.7 mg mL −1 (Conidi et al, 2014) and olive mill wastewaters of 211.80 mg mL −1 (Garcia-Castello et al, 2010). Similar content compared to our study was observed by Cassano et al (2013), 1409 mg mL −1 in terms of total polyphenols in olive mill wastewaters.…”
Section: Nejayote Compositionmentioning
confidence: 95%
“…polyphenols are widely used by pharmaceutical, cosmetic and food sectors (Garcia-Castello et al, 2010) due to their properties such as anti-inflamatory, antimicrobic and antioxidant activity as well as inhibition of oxidative damage and the radical elimination (Ranalli et al, 2003;Bisignano et al, 1999;Obied et al, 2005). These compounds are usually synthesized by chemical methods that are responsible of their high price as well as their low yields obtained (Conidi et al, 2014). On the other hand, an integrated membrane process can be used for the fractionation by NF membranes or concentration using Reverse osmosis.…”
Section: 5mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the nixtamalization waste waters should be considered a valuable source of high-value-added compounds. Some other types of waste water from the food-processing industry have been considered for recovery of polyphenols: artichoke waste waters Table 3 The final mass balance for total soluble solids (TSS), carbohydrates, polyphenols, total organic carbon (TOC), and calcium content in the clarified nixtamalization waste water processed by means of the ultrafiltration (UF) membrane (does not let 1-kDa compounds through) [25], olive mill waste waters [11], and orange press liquor [8]. As for the retentate, it can be reused in other possible applications because the concentrated retentate is rich in calcium; thus, this retentate can be subjected to another nixtamalization process as an alkaline solution.…”
Section: Retention Of Compounds By the Uf (1-kda) Membrane: Total Masmentioning
confidence: 99%
“…[14]. A very interesting study about membrane technology and the valorization of artichoke wastewaters (leaves, stems, bracts, and blanching waters) has been recently published [15]. In this work, pressure-driven membrane processes, such as ultrafiltration, nanofiltration, and reverse osmosis, have been successfully employed for the purification and concentration of bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%